Resepsi Mu’tazilah pada Dinasti Abbasiyah - Febriani, Fenti (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to see how the Muktazilah school played a major role during the Ummayah and Abbasid dynasties by using qualitative methods through a literature research approach, this article aims to look at the political development of the Abbasid Caliphate which was full of ups and downs. It started when the rebels (Mu'tazilah and Shi'a) jointly overthrew the Umayyad caliphate and ended with the fall of Baghdad in the hands of the Mongols. But behind his political struggle, the Mu'tazilah were able to build a strong foundation to spread his teachings, especially to place influential people in the palace. During the caliphate of al-Ma'mun, al-Mu'tashim, and al-Watsiq, the Mu'tazilis gained a strategic position in the Abbasid government, and because of that, controlled state policy. This article tries to reveal how the Mu'tazilites rose in influence in the internal policies of the state to the top, (especially during the mihnah period), and how their glory faded away. This fact led the writer to conclude that Wasil bin 'Atha's (founder of Mu'tazilah) strategy brought the Mu'tazilah to the peak of their political influence. Meanwhile, the controversy surrounding the mihnah itself played a role in the antipathy of the Abbasid people.